Decent work in non-financial reporting of Russian companies: Assessing the disclosure quality - Evgeniya V. Nekhoda; Nurali U. Arabov; Aleksandr L. Bogdanov; Maria V. German; Tatyana V. Kuklina (Управленец, 2022)
Non-financial reporting is the key institution for monitoring the provision of decent work for employees. The analysis of Russian companies’ reports has shown that the low quality of decent work disclosures is attributed to the lack of data and collection and calculation methods. The article examines the current practices for evaluating non-financial reporting, presents the author’s approach to assessing the quality of decent work disclosures and reveals the relationship between the completeness of disclosed information and companies’ performance. Methodologically, the study rests upon the concept of corporate governance. Among the research methods used are quantitative, qualitative (content) and statistical analysis. The proposed assessment approach was tested at metallurgical and mining enterprises, which allowed identifying main gaps between the companies’ ranking positions and the practical provision of decent work for employees. A positive relationship was revealed between the completeness of disclosed information about decent work and the companies’ financial performance as well as labor productivity. The authors come up with recommendations for state regulation in the field of non-financial reporting. The proposed approach allows conducting a fair assessment of the depth of disclosure in non-financial reporting and comparing the levels of provision with decent work in different companies, which together will contribute to improving the effectiveness of the positioning strategy and formation of its unique socially oriented image.